Evaluation of the degree of carbonation of concretes in three environments. (10th January 2020) - Andrade, C.
Highlights: "Degree of carbonation" DoC, is a different concept than the depth of carbonation. The DoC, is not higher when higher is the carbonation depth. They are independent. DoC depends on the concrete humidity being highest in natural non-sheltered conditions. After 2 years the DoC is independent of the age of the concrete. Abstract: Cement manufacture is contributing to CO2 emissions as calculated by the Intergovernmental Panel for Climatic Change of 520 kg of CO2 per tonne of clinker. However, hydrated cement phases in concrete, absorb CO2 through the carbonation of cement paste. Recently several studies have been published on the CO2 uptake assuming a theoretical degree of carbonation, DoC, and multiplying it by the amount of concrete produced in the country, as made in the Annex BB of standard EN 16757 for the European Environmental Declarations. Present paper shows a study made in Spain on the CO2 uptake during 4 years with two types of concretes, fifteen cements and three environments. The statistical analysis of the results indicated an average value of the degree of carbonation (DoC) for all cement types, except those containing high proportions of GGBS, of around 62.5% with a lower limit of 23% for the lower 5% fractile in the representation of the statistical distribution of values as a normal distribution.